1980
DOI: 10.1111/j.1476-5381.1980.tb10898.x
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Sodium Cromoglycate on ‘C’ Fibre Endings in the Dog Lung

Abstract: The effect has been studied of sodium cromoglycate (SCG) on the activity of ‘C’ fibre sensory nerve endings in the canine lung. Pretreatment with SCG (100 μg/kg i.v.) reduced the excitation of these endings by capsaicin (10 μg/kg i.v.) for approximately 45 min. This property of SCG may explain its ability to suppress certain types of bronchoconstrictor responses in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
2

Year Published

1983
1983
2003
2003

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(71 citation statements)
references
References 11 publications
2
67
2
Order By: Relevance
“…Moreover, pharmacological evidence suggests that tachykinins could participate in the pathogenesis of airflow obstruction induced by isocapnic dry gas hyperpnoea in human subjects with asthma. Indeed, sodium cromoglycate which inhibits C-fibres discharge (Dixon et al, 1980) and thus the release of tachykinins or the tachykinin receptor antagonist, SCH 37224 (Solway & Leff, 1991) blunt hyperpnoea-induced broncho-obstruction in asthma. Similarly, it has been suggested that VIP and related peptides released from airway cholinergic nerves may also play a role in asthma (Barnes, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pharmacological evidence suggests that tachykinins could participate in the pathogenesis of airflow obstruction induced by isocapnic dry gas hyperpnoea in human subjects with asthma. Indeed, sodium cromoglycate which inhibits C-fibres discharge (Dixon et al, 1980) and thus the release of tachykinins or the tachykinin receptor antagonist, SCH 37224 (Solway & Leff, 1991) blunt hyperpnoea-induced broncho-obstruction in asthma. Similarly, it has been suggested that VIP and related peptides released from airway cholinergic nerves may also play a role in asthma (Barnes, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the response to methoxamine was not observed in the absence of atropine, in which case bronchoconstrictor responses may well have been greater. The dose of ipratropium bromide used in the present study is sufficient to block a standard methacholine challenge (Woolcock et cold air (Breslin et al, 1980) SO2 (Harries et al, 1981) and hypotonic nebulized solutions in man (Fuller & Collier, 1984) and that following stimulation of reflex arcs in dogs (Dixon et al, 1980 (Tattersfield, 1981). There was no significant difference between the mean values for FEV, after the three pretreatments.…”
Section: Discussionmentioning
confidence: 63%
“…Sodium cromoglycate inhibits unmyelinated afferent vagal pathways in dogs (Dixon et al, 1980) and in some species bradykinin causes bronchoconstriction by activation of C-fibre sensory nerve endings (Kaufman et al, 1980). This suggests that sodium cromoglycate and nedocromil sodium may inhibit sensory activation by bradykinin.…”
Section: Discussionmentioning
confidence: 94%